Solving the boundary problems for biharmonic operator by using the conformable fractional derivative method - Ahmedov, Anvarjon A.; Siti Fatimah, Ahmad Zabidi; Turmetov, Batirkhan (Universiti Malaysia Pahang, 2018)
There are various methods for constructing solutions of differential equations of fractional order. In the papers the operational method of construction of the solution of the linear differential operators with constant coefficients were considered. The explicit form of the solution of the equation is found by transforming the problem to the equivalent integral equation.